Fitososiologi Hutan Pegunungan di Lereng Tenggara Gunung Salak - Mirmanto, Edi (Perhimpunan Biologi Indonesia, 2014)
A phytosociological study has been conducted in the south-east slope of Mount Salak, Sukabumi, West Java.Vegetation data were analyzed using 21 plots made of 30 m x 30 m which covered various habitat conditions. Atotal of ninety seven tree species (dbh. Ã¢â°Â¥ 10 cm) were recorded belonging to 72 genera and 39 families. The mostdominant families occurred in the study area were Fagaceae, Hammamelidaceae and Euphorbiaceae, followed byTheaceae, Meliaceae and Sapindaceae. The dominance of those families was apparently from the contribution ofthe most dominant species Altingia excelsa and the other species such as the Schima wallichii, Castanopsis javanica,Pometia pinnata, and Lithocarpus korthalsii. Spatial distribution of the vegetation is affected by altitude and/orhabitat slope which develop forest community patterns, such as lowland forest, lower and upper slope forests, aswell as lower and upper mountain forests. The distribution of tree species also follows this pattern, i.e certainspecies only occur on certain (specific) habitat type.Keywords: species ekology, Gunung Halimun-Salak National Park, phytosociology